Patogenisitas Isolat Beauveria bassiana dan Metarhizium anisopliae asal Tanah Lebak dan Pasang Surut Sumatera Selatan untuk Agens Hayati Scirpophaga incertulas - Rosdah Thalib; Redi Fernando; . Khodijah; Dewi Meidalima; Siti Herlinda (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Pathogeicity of Beauveria bassiana and Metarhizium anisopliae Isolates from Fresh Swamp and Tidal Lowland, South Sumatra for Scirpophaga incertulas Biological Agents. The objectives of the research weret o explore and to determine the pathogenicity of entomopathogenic fungi againts the larvae of Scirpophaga incertulas, and to measure conidial viability and density of the fungi. The method for fungi exploration used larvae of Tenebrio molitor baiting submerged in the soil. The soil was taken from fresh swampand tidal lowland rice in South Sumatra. From the exploration study, we found two species of entomopathogenic fungi: Beauveria bassiana and Metarhizium anisopliae. Mortality of S. incertulas larvae that had been treated topically with fungal conidia (1x106 conidia ml-1) varied among the isolates. The highest mortality (98.33%) caused by BPlus isolate of B. Bassiana and the lowest by MtmIn isolate of M. anisopliae (57.50%) and BTmTr isolate of B. bassiana (57.50%). The fungal colonies grew fast from the second day up to the fourth day after incubation but the growth became slow after the fifth day. The highest conidial density was resulted by BPcMs of B. bassiana isolate (63.33x106 conidia ml-1) but this density was not significantly different from that of the BPlus of B. bassiana isolate (63.11x106 conidia ml-1). The lowest conidial density found in BTmTr of B. bassiana isolate (20.97x106 conidia ml-1) . The isolate B. bassiana was more effective than M. anisopliae againt the larvae of S.incertulas.